Nicotinic Acid Adenine Dinucleotide Phosphate Induces Intracellular Ca2+ Signalling and Stimulates Proliferation in Human Cardiac Mesenchymal Stromal Cells - Faris, Pawan; Casali, Claudio; Negri, Sharon; Iengo, Lara; Biggiogera, Marco; Maione, Angela Serena; Moccia, Francesco (Frontiers in Cell and Developmental Biology, 2022)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a newly discovered second messenger that gates two pore channels 1 (TPC1) and 2 (TPC2) to elicit endo-lysosomal (EL) Ca2+ release. NAADP-induced lysosomal Ca2+ release may be amplified by the endoplasmic reticulum (ER) through the Ca2+-induced Ca2+ release (CICR) mechanism. NAADP-induced intracellular Ca2+ signals were shown to modulate a growing number of functions in the cardiovascular system, but their occurrence and role in cardiac mesenchymal stromal cells (C-MSCs) is still unknown. Herein, we found that exogenous delivery of NAADP-AM induced a robust Ca2+ signal that was abolished by disrupting the lysosomal Ca2+ store with Gly-Phe β-naphthylamide, nigericin, and bafilomycin A1, and blocking TPC1 and TPC2, that are both expressed at protein level in C-MSCs. Furthermore, NAADP-induced EL Ca2+ release resulted in the Ca2+-dependent recruitment of ER-embedded InsP3Rs and SOCE activation. Transmission electron microscopy revealed clearly visible membrane contact sites between lysosome and ER membranes, which are predicted to provide the sub-cellular framework for lysosomal Ca2+ to recruit ER-embedded InsP3Rs through CICR. NAADP-induced EL Ca2+ mobilization via EL TPC was found to trigger the intracellular Ca2+ signals whereby Fetal Bovine Serum (FBS) induces C-MSC proliferation. Furthermore, NAADP-evoked Ca2+ release was required to mediate FBS-induced extracellular signal-regulated kinase (ERK), but not Akt, phosphorylation in C-MSCs. These finding support the notion that NAADP-induced TPC activation could be targeted to boost proliferation in C-MSCs and pave the way for future studies assessing whether aberrant NAADP signaling in C-MSCs could be involved in cardiac disorders.